Macroeconomic factors and bank specific characteristics affecting bank performance - a panel analysis on commercial banks in 5 ASEAN economies: Indonesia, Malaysia, Singapore, Thailand and Vietnam. - Nguyen, Thi Thu Thuy (2011)
ABSTRACT This dissertation is carried out with the aim of examining macroeconomic factors and bank specific characteristics affecting bank performance which is measured in two aspects: profitability and risk exposure. Using the a panel data of commercial banks in five ASEAN economies: Indonesia, Malaysia, Singapore, Thailand and Vietnam across the period from 2004 to 2010, the quantitative analysis methods confirm that bank profitability is negatively associated with bank risk exposure, which is consistent with existing empirical evidence. The study also presents the evidence that stronger liquidity position significantly contributes to increase bank profitability (assessed by ROAA and ROAE) and reduce bank risk (measured by the ratio of LLP to total loans). In addition, the commercial banks’ performance is also influenced by market concentration. Banks exhibit less profit in a more competitive environment. However, the factor will help to reduce bank risk exposure and introduce more stability into the sector. With regard to economic growth, when further investigation into the period of prior and post - the global financial crisis is conducted, the indicator displays significantly negative relationship with bank risk. The results also suggest that the magnitude of this influence is much greater in boom time than in slowdown period. The dissertation fills a gap in the literature of determinants of commercial banks’ performance in Southeast Asia. Moreover, it may be beneficial to bankers and policy makers of these five ASEAN economies in making decision to boost the bank profitability without resulting in higher risk exposure.